Analyzing Performance of Skill Development Programs in India - Singh, Jalbir; Aggarwal, Renu; Gupta, Pankaj Kumar (Prabandhan: Indian Journal of Management, 2025)
Purpose : The study analyzed the effectiveness of selected state-run skills development schemes, particularly the socioeconomic impact of the selected skill development schemes on beneficiaries. Methodology : The study conducted a questionnaire-based survey of 655 respondents who attended the skill development programs (SDPs) during the sample period. PLS-structural equation modeling (SEM) was adopted to examine the performance of SDPs, the hypothesized relationship among the dependent variables, i.e., income attainment, educational attainment, employability, entrepreneurship, work performance, and challenges to the implementation of SDP and skill attainment as the independent variable. Findings : We found that SDPs are not sufficiently blended with employment opportunities to enhance their effectiveness by enhancing industry collaborations and career counselling in these programs, which can increase placement rates. There is a significant need to raise awareness and improve the implementation of skill development initiatives to maximize their reach and impact, especially for women. The region’s industrial profile should be considered when customizing skill programs at the state level to ensure that training meets the unique requirements of regional industries. Practical Implications : The study recommended that SDPs must be integrated with available employment opportunities to make them more effective. An SDP must be evaluated for different motives from all stakeholders, primarily industry, trainees, government, civil society, and especially workforce market requirements, which are crucial. Our study is not free from limitations and allows scope for future researchers, whether these include differences in the design and assessment models of the other state-run SDPs and diversity in multiple regional and cultural contexts, requiring localised understanding. Originality : The study represents path-breaking research for the state of Haryana and has implications for the proposed skill development policy of the Government of India.